(untitled) (Sukuna Journal, 2026)
Education refers to the learning process. It depends upon the development of society and the advancement of Technology. The advancement of Technology has significantly transformed the educational System as well as the learning process across the world. This Study is an analysis of the transformation of education in Nepal in the context of change in the political, social, and structural position of the nation. This research presents the situation of school education reform in Nepal during the period from traditional Schooling to the modern digital and interactive stage. From the traditional Gurukul System, the chalk and blackboard teaching system has already transformed into a digital and interactive learning System; in this way, education has undergone a paradigm shift. This Study explores how technological developments is transformed the education system and how does education govern the new environment of modern advancement, such as Artificial Intelligence, Virtual Reality, Learning Management Systems, etc. The digital pedagogy has influenced the structure, accessibility, and Quality of education. The Study presents the opportunity and threat related to the field of educational transformation based on the use of Technology and the new educational policy governed in the Nepalese context. .